PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE (STAD) TERHADAP HASIL BELAJARMATEMATIKA SISWA MTs. NURUL WATHAN PLAMBIK TAHUN PELAJARAN 2017/2018 - Sabrun Sabrun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2018)
The problem in this research is the low of student learning result of mathematics. This is caused by the teaching method used by the is still monoton. The purpose of this research is to know the effect of cooperative learning model of Student Teams Achievement Division (STAD) type toward the result of learning mathematics of VII student of MTs. Nurul Wathan Plambik. The type of research used in this study is Quaisi Experimentand researchdesign is pretest – posttest Control Group Design. Population in this research is class VII MTs. Nurul Wathan Plambik. The sampel of the research is class VIIA as experiment class and VIIB as control class. The sampling technique uses saturated sampling. The instrument of this research is the test result sheet. Based on the result of data analysis of student learning outcomes obtained the average value in the experiment class of 81,33 with the highest value of 100 and the lowest 65, while the average value in the control class of 60,17 with the highest value of 80 and the lowest value of 40. Based on t test result obtained tcount of 8,298 and ttable of 2,002, because tcount  ttable then Ha accepted and Ho rejected. So it can be concluded that there is effect of Cooperative Learning Model Type Student Teams Achievement Division (STAD) On Learning Result Mathematics Student Class VII Mts. Nurul Wathan Plambik Year Lesson 2017/ 2018.